Coalescence Deformation of Bubble Pairs Generated from Twin Nozzles in CMC Solutions. Issue 10 (16th August 2016) - Fan, Wenyuan; Qi, Tong; Sun, Yawei; Zhu, Ping; Chen, Hui
Abstract: A coupled level‐set/volume‐of‐fluid method, under the consideration of the rheological characteristics of a fluid, is employed to investigate numerical coalescence deformation of bubble pairs generated at two adjacent nozzles in carboxymethyl cellulose aqueous solutions. The satisfactory agreement between numerical results and experimental measurements proves the validity of this approach in predicting the surface evolution of bubbles. Simulated results show that the bubble coalescence process involves four stages of independent growth, rapid mergence, radial expansion, and vertical stretching. The various effects of surfactant concentration, gas flow rate, nozzle spacing, and nozzle diameter on the aspect ratio depend greatly on each coalescence period. Abstract : Understanding coalescing bubble deformation in non‐Newtonian fluids is crucial for optimizing gas‐liquid equipment design and for gaining an insight into multibubble behavior. Rheological characteristics of fluids are considered in numerical investigations of the coalescence regime of two bubbles generated at adjacent nozzles.